MODAL SOSIAL PEREMPUAN DALAM MENJAGA KELESTARIAN HUTAN - Zikrillah, Muhammad; Afriana, Fitra; Putri, Rani; Yunus, Saifuddin (Program Studi Administrasi Bisnis, 2021)
The magnitude of the pressure on the use of forest resources in the Gunung Leuser National Park (TNGL) forest area has caused the forest area to be in an alarming condition due to the high rate of deforestation caused by encroachment and illegal logging activities. This condition has a negative impact on the lives of people living in the surrounding area, especially women, so that women are aware of the need to participate in forest conservation activities. This paper describes how the social capital owned by women in Damaran Village, Bener Meriah Regency makes it an effective basis for their role in preserving the ecosystem in the GLNP forest area. The method used is the Literature method. The results showed that women in Damaran Village, Bener Meriah Regency related to their role in preserving the TNGL forest supported by an effectively built social capital base, in which there are main elements of social capital in the form of mutual trust (Trust) towards the ability of members, values and supporting norms that regulate the behavior (Norms) of Ranger members in disseminating awareness of forest conservation to the community, and the formed network (Network) in building communication and cooperation with parties outside themselves.